Analisis Perbandingan Performa Bahan Bakar Shell Super dan Shell V-Power pada Motor Honda PCX 150 cc Tahun 2021 - Syahrir, Irwan; Dwi Priyono, Muslih; Batutah , Moh. Arif (Universitas Muhammadiyah Surabaya Publishing, 2024)
The type of fuel used greatly influences vehicle performance. This research aims to determine the performance of Shell Super and Shell V-Power fuel in terms of torque, power, fuel consumption, specific fuel consumption, average pressure and thermal efficiency. Test results using a dynotest show that the maximum power of 15.7 hp occurs when using Shell Super fuel when the engine speed is 9000 rpm. The highest Brake Specific Fuel Consumption is 2,182 x 10-4 Kg/HP Hour when using V-Power shell fuel at an engine speed of 3000 rpm. The highest Brake Mean Effective Pressure, namely 1046.343 kPa, was obtained when using Shell Super fuel at an engine speed of 9000 rpm, while the highest torque, namely 12.44 N.m, occurred when the engine speed was 9000 rpm when using Shell Super fuel. The highest efficiency was obtained at 92.2% when using Shell V-Power fuel at an engine speed of 7000 rpm.